1992
DOI: 10.1073/pnas.89.24.12053
|View full text |Cite
|
Sign up to set email alerts
|

Distinct promoters direct neuronal and nonneuronal expression of rat aromatic L-amino acid decarboxylase.

Abstract: Aromatic L-amino acid decarboxylase (AADC, EC 4.1.1.28) catalyzes the decarboxylation of L-dopa to dopamine in catecholamine cells and 5-hydroxytryptophan to serotonin in serotonin-producing neurons. This enzyme is also expressed in relatively large quantities in nonneuronal tissues such as liver and kidney, where its function is unknown. Neuronal and nonneuronal tissues express AADC mRNAs with distinct 5' untranslated regions. To understand how this is accomplished at the genomic level, we have isolated rat g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…dTdc2 Is Expressed throughout the CNS and Provides Extensive Innervation to the Female Reproductive Tract, whereas dTdc1 Is Expressed Nonneurally-In Drosophila, as in other animals, each decarboxylase is typically encoded by one gene, although distinct promoters and/or alternative splicing may direct expression of neural and nonneural products, as is the case for the Drosophila DOPA decarboxylase and mammalian AADCs (21)(22)(23). Since there appear to be two TDCs in the Drosophila genome, we examined their expression patterns to determine whether they had unique or overlapping distributions.…”
Section: Resultsmentioning
confidence: 99%
“…dTdc2 Is Expressed throughout the CNS and Provides Extensive Innervation to the Female Reproductive Tract, whereas dTdc1 Is Expressed Nonneurally-In Drosophila, as in other animals, each decarboxylase is typically encoded by one gene, although distinct promoters and/or alternative splicing may direct expression of neural and nonneural products, as is the case for the Drosophila DOPA decarboxylase and mammalian AADCs (21)(22)(23). Since there appear to be two TDCs in the Drosophila genome, we examined their expression patterns to determine whether they had unique or overlapping distributions.…”
Section: Resultsmentioning
confidence: 99%
“…This example of alternative splicing in exon 1B versus exon 1C yields multiple RNA transcripts and has also been described for exon 9 in the human PS-1 gene (16). Two distinct transcription start sites, however, have been reported for only a few genes including human catechol-O-methyl transferase (24), mouse neurotrophin-3 (25), and rat aromatic Lamino acid decarboxylase (26). In these cases, each transcriptional start site was associated with a distinct promoter so that a stoichiometry of one promoter per transcription start site was observed.…”
Section: Discussionmentioning
confidence: 99%
“…While the coding region is identical in both forms, liver and kidney AADC mRNA contains a short 5Ј-untranslated region (UTR) which is entirely unrelated to the 5Ј-UTR found in AADC mRNA expressed in tissues of neuronal origin. We have previously shown that, within the rat AADC gene, dual promoters direct the expression of these tissue-specific forms of AADC mRNA resulting in the alternative use of two untranslated exons (9). This has also been shown by others for the rat (10) and human (11-13) AADC gene.…”
mentioning
confidence: 93%
“…The AADC Nonneuronal Promoter Directs Tissue-specific Expression of the Luciferase Reporter Gene-We have previously identified the location of the nonneuronal transcription start site of the rat AADC gene (9). To identify cis-acting elements in the nonneuronal AADC promoter, 1111 bp of the region 5Ј of this transcription start site were placed upstream of the firefly luciferase reporter gene in the pGL2 basic vector expression ( Fig.…”
Section: Llc-pk 1 Cells Express the Nonneuronal Form Of Aadc Mrna-mentioning
confidence: 99%
See 1 more Smart Citation